Catastrophe Bond Diversification Strategy Using Probabilistic–possibilistic Bijective Transformation And Credibility Measures In Fuzzy Environment - Wulan Anggraeni; Sudradjat Supian; Sukono; Nurfadhlina Abdul Halim (MDPI, 2024)
Indexed by WOS